Hepatozoon spp. em carnívoros neotropicais presentes em vida livre no Parque Nacional das Emas, em Goiás, Brasil - Metzger, Betina [UNESP] (2013)
The aim of this study was to investigate the occurrence of Hepatozoon spp. in free ranging neotropical carnivores from Brazil. 158 blood samples were analyzed from Canidae, Procyonidae and Mephitidae from Emas National Park, in the State of Goias, Brazil. From the sampling total, 75 were obtained from Chrysocyon brachyurus (maned wolf), 65 from Cerdocyon thous (crab-eating dog), 10 from Conepatus semistriatus (striped hog-nosed skunk), 06 from Lycalopex vetulus (hoary fox) and two from Nasua nasua (South American coati). Hepatozoon spp. were diagnosed by Polymerase Chain Reaction (PCR) after DNA was extracted. From the total analyzed, 63.92% samples were parasitized by Hepatozoon; and from the positive samples 41.14% were collected from C. brachyurus, 18.35% from C. thous, 3.79% from L. vetulus and 0.63% from N. nasua. The majority of C. brachyurus population (86.66%) was infected and also 44.61% of C. thous and 100% of L. vetulus studied. Molecular characterization of the isolates was performed after sequencing and phylogenetic analyses. These demonstrated that the isolates from C. thous and the majority of the ones from C. Brachyurus showed high similarity with Hepatozoon sp. from C. thous from the State of Espirito Santo and also with Hepatozoon americanum. The isolate of N. nasua showed similarity with H. felis; and the ones from L. vetulus with H. canis from domestic dog. The molecular identification of Hepatozoon sp. from N. nasua as well as the infection by this hematozoa in free ranging C. brachyurus and L. vetulus are novelties in the world